Functional foods and biotechnology : sources of functional foods and ingredients - Shetty, Kalidas; Sarkar, Dipayan (Milton : CRC Press LLC, 2019)
The first of two related books that kick off the Food Biotechnology series, Functional Foods and Biotechnology: Sources of Functional Foods and Ingredients, focuses on the recent advances in the understanding of the role of cellular, metabolic, and biochemical concepts and processing that are important and relevant to improve functional foods and food ingredients targeting human health benefits. This volume explores sources of ecologically-based diversity of functional foods and food ingredients that are available to enhance diverse nutritional values and functional benefits of foods for better human health outcomes, especially focusing on emerging diet and lifestyle-linked non-communicable chronic disease (NCDs) challenges. The contributors with expertise in the field of Food Biotechnology and Functional Food Ingredients have integrated the recent advances in some common as well as novel sources of functional foods and ingredients from diverse ecological and cultural origins. Further, these chapters also highlight human health relevant bioactive profiles and associated functionalities of these health-promoting compounds, including preventative functional roles for common NCD-linked health benefits. FEATURES: Provides ecological and metabolic rational to integrate novel functional food and functional ingredient sources in wider health-focused food system innovations. Examines the value-added role of select functional foods and food ingredients to improve NCD-linked health benefits such as type-2 diabetes, cardiovascular disease, and human gut improvement Includes insights on system-based solutions to advance climate resilient and health focused food diversity based on diverse biotechnological approaches to design and integrate functional food and food ingredient sources Overall, the rationale of this book series is focused on Metabolic-Driven Rationale to Advance Biotechnological Approaches for Functional Foods, the synopsis of which is presented as the Introduction chapter, which is followed by a chapter on current understanding about regulatory guidelines for health claims of functional foods and food ingredients. Special topics on nonnutritive sweeteners, caroteneprotein from seafood waste, and Xylooligosaccharides as functional food ingredients for health-focused dietary applications are integrated in this book. Additionally, ecologically and metabolically-driven functional roles of common food sources such as corn, and barley and some novel food sources, such as ancient emmer wheat, black soybean, fava bean, herbs from Lamiaceae and functional protein ingredients and minerals from Lemnaceae are also highlighted in this volume. The overall goal is to provide insights on role of these functional food and ingredient sources for their integration in wider health-focused food systems, which will help food scientists, food industry personnel, nutritionists, crop science researchers, public health professionals, and policy makers to make appropriate decisions and to formulate strategies for improving health and well-being. A related book focuses on biological and metabolically driven mobilization of functional bioactives and ingredients and their analysis that is relevant in health and wellness.
4.2 Ancient Wheat and Its Importance in Modern-Day Food Systems -- 4.3 Emmer, an Ancient Cereal Grain -- 4.3.1 Emmer as a Resilient Food Crop for Adverse Climatic Conditions -- 4.3.2 Emmer as a Food Crop for Human Health -- 4.3.2.1 Emmer and Its Antioxidant Activity -- 4.3.2.2 Emmer and Its Anti-Hyperglycemic Activity -- 4.4 Food Synergies and Fermentation to Improve the Functionality of Ancient Wheat -- 4.4.1 Ancient Wheat as a Probiotic and Prebiotic Food Ingredient for Human Health -- 4.4.2 Wheat Fermentation and Its Antimicrobial Activity for Human Health
Description based upon print version of record.
5.3 Biological Effects of Barley Phytochemicals Relevant to Human Health Benefits
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Nutrition; TECHNOLOGY / Food Science; Food -- Biotechnology; Functional foods